2009
DOI: 10.1007/s00134-009-1447-y
|View full text |Cite
|
Sign up to set email alerts
|

Bedside estimation of recruitable alveolar collapse and hyperdistension by electrical impedance tomography

Abstract: We described an EIT-based method for estimating recruitable alveolar collapse at the bedside, pointing out its regional distribution. Additionally, we proposed a measure of lung hyperdistension based on regional lung mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
334
0
29

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 381 publications
(386 citation statements)
references
References 25 publications
3
334
0
29
Order By: Relevance
“…98 Electrical impedance tomography has the potential for bedside use to estimate regional alveolar collapse and overdistention. [98][99][100][101][102][103] To date, experience with electrical impedance tomography in North America is limited.…”
Section: Imagingmentioning
confidence: 99%
“…98 Electrical impedance tomography has the potential for bedside use to estimate regional alveolar collapse and overdistention. [98][99][100][101][102][103] To date, experience with electrical impedance tomography in North America is limited.…”
Section: Imagingmentioning
confidence: 99%
“…Therefore the knowledge of lung recruitability may impact the mechanical ventilation setting [11]. Different methods such as the pressure-volume curve of the respiratory system [5,6], the use of electrical impedance tomography [8,31], nitrogen washout/washin technique [32], and transthoracic lung ultrasound [9] have been proposed to estimate lung recruitability [4]. Although lung CT scan requires the transportation of patients and exposure to radiation, it remains the reference method for assessing lung recruitability [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, it may underestimate lung recruitment in patients with focal aeration loss [7]. Electrical impedance tomography provides noninvasive real-time imaging of pulmonary inflation which could predict the lung recruitability [8], but it computes only a small fraction of the lung and is affected by the movements of intrathoracic blood due to the application of PEEP. Recently, Bouhemad et al [9] showed that PEEPinduced lung recruitment estimated by transthoracic lung ultrasound was related to the one computed by the pressure-volume curves.…”
Section: Introductionmentioning
confidence: 99%
“…Alimentos ou líquidos de condutividade conhecida podem ser usados como contraste [23] para medir não só a velocidade de esvaziamento gástrico como também a motilidade gástrica [24]. Outra aplicação comum da TIE é o monitoramento da função pulmonar [25][26][27][28], incluindo a geração de imagens de ventilação e perfusão pulmonares, a investigação de embolia pulmonar, derrames e efeitos da ventilação mecânica. Além dessas aplicações, podem-se citar ainda o monitoramento do sistema circulatório [28][29][30][31] e a detecção de câncer de mama [32].…”
unclassified
“…A detecção de algumas alterações pulmonares já é feita com o uso de TIE, como a detecção de pneumotórax [25] e colapso alveolar [26], mas são baseadas em imagens de diferenças da caixa torácica e, por isso, é necessário que a monitorização seja iniciada antes do aparecimento da alteração pulmonar. A obtenção de imagens absolutas tridimensionais do pulmão pode possibilitar a detecção e localização dessas alterações nos casos em que a condição já existia antes do início da monitoração com TIE.…”
unclassified